Impact of Denture Cleaning Method and Overnight Storage Condition on Denture Biofilm Mass and Composition: A Cross-Over Randomized Clinical Trial. - Joke Duyck; Katleen Vandamme; Stefanie Krausch-Hofmann; Lies Boon; Katrien De Keersmaecker; Eline Jalon; Wim Teughels (PLoS ONE)
Background Appropriate oral hygiene is required to maintain oral health in denture wearers. This study aims to compare the role of denture cleaning methods in combination with overnight storage conditions on biofilm mass and composition on acrylic removable dentures. Methods In a cross-over randomized controlled trial in 13 older people, 4 conditions with 2 different mechanical cleaning methods and 2 overnight storage conditions were considered: (i) brushing and immersion in water without a cleansing tablet, (ii) brushing and immersion in water with a cleansing tablet, (iii) ultrasonic cleaning and immersion in water without a cleansing tablet, and (iv) ultrasonic cleaning and immersion in water with a cleansing tablet. Each test condition was performed for 5 consecutive days, preceded by a 2-days wash-out period. Biofilm samples were taken at baseline (control) and at the end of each test period from a standardized region. Total and individual levels of selected oral bacteria (n = 20), and of Candida albicans were identified using the Polymerase Chain Reaction (PCR) technique. Denture biofilm coverage was scored using an analogue denture plaque score. Paired t-tests and Wilcoxon-signed rank tests were used to compare the test conditions. The level of significance was set at α< 5%. Results Overnight denture storage in water with a cleansing tablet significantly reduced the total bacterial count (p<0.01). The difference in total bacterial level between the two mechanical cleaning methods was not statistically significant. No significant effect was observed on the amount of Candida albicans nor on the analogue plaque scores. Conclusions The use of cleansing tablets during overnight denture storage in addition to mechanical denture cleaning did not affect Candida albicans count, but reduced the total bacterial count on acrylic removable dentures compared to overnight storage in water. This effect was more pronounced when combined with ultrasonic cleaning compared to brushing. Trial registration ClinicalTrials.gov NCT02454413.